IMPORTANCE OF INCREASING KNOWLEDGE OF EXCLUSIVE BREASTFEEDING AS AN EFFORT TO PREVENT STUNTING - Kurniawati, Ratna Dian; Afifah Nurul Salsabila; Supriyatni (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2022)
Exclusive breastfeeding is a perfect source of nutrition for babies containingall the nutritional components to meet the baby health in ideal baby growth and development. The low level of exclusive breastfeeding can have an impact on the decline in the baby's immune system and health. The phenomenon is that not all postpartum mothers want to give exclusive breastfeeding. Some refuse on the grounds of working, spoiling their appearance, breast milk does not come out, and other reasons related to myths about breastfeeding. This study aimed to determine the effect of leaflet media counseling on knowledge of exclusive breastfeeding for infants in Cisaranten Kidul Village. The method in this research is quantitative with a quasi-experimental design. The research sample was 50 mothers with babies divided into twogroups. Sampling technique using Purposive Sampling. Data analysis through Wilxocon. The results showed an increase in knowledge before and after being given counseling by 13.45%. The Wilxocon test analysis is 0.00 < 0.05, which means that leaflet media counseling has an effect on increasing knowledge of exclusive breastfeeding. Efforts to increase understanding of exclusive breastfeeding must continue to pursue to increase the coverage of exclusive breastfeeding as an indicator of clean and healthy living behavior and prevent stunting for a stunting-free generation. There is a need for cross-program and cross-sector collaboration that enhances partnerships in increasing knowledge about the importance of exclusive breastfeeding.